57 years of research and memory of the Pacopampa Archaeological Project of the ISHRA the Universidad Nacional Mayor de San Marcos - Morales Chocano, Daniel (2025)
This paper presents a state-of-the-art (from 1968 to 2004) of the archaeological research carried out on the Pacopampa archaeological project, a Formative Period site in the Central Andes, in the province of Chota-Cajamarca, Peru, marking the 57th anniversary of its inception within the Andean Rural History Seminar Institute of the UNMSM.